2023
DOI: 10.3390/polym15132872
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Bio-Based PLA/PEG/g-C3N4 Low-Temperature Composite Phase Change Energy Storage Materials

Abstract: As energy and environmental issues become more prominent, people must find sustainable, green development paths. Bio-based polymeric phase change energy storage materials provide solutions to cope with these problems. Therefore, in this paper, a fully degradable polyethylene glycol (PEG20000)/polylactic acid (PLA)/g-C3N4 composite phase change energy storage material (CPCM) was obtained by confinement. The CPCM was characterized by FTIR and SEM for compatibility, XRD and nanoindentation for mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In the second area, i.e., PCMs shape stabilization, bio-based polymers are applied to limit PCM leakage during the phase transition, but can also improve selected properties, such as thermal conductivity, as well as shape stability which is of primary In PEG20,000/PLA/graphitic carbon nitride (g-C3N4) composite PCM, prepared using the confinement method, PEG hinders the crystallization of PLA, and it was confirmed using the XRD method. The authors found that the incorporation of PEG changed the number of diffraction peaks of PLA, suggesting disrupted PLA crystallization, and in consequence a decrease in hardness [29]. The composite PCM exhibited a heat of phase transition of 106.1 kJ/kg for PLA:PEG:g-C3N4 with a mass ratio 3:6:1, and an increased thermal conductivity compared to PLA.…”
Section: Discussionmentioning
confidence: 99%
“…In the second area, i.e., PCMs shape stabilization, bio-based polymers are applied to limit PCM leakage during the phase transition, but can also improve selected properties, such as thermal conductivity, as well as shape stability which is of primary In PEG20,000/PLA/graphitic carbon nitride (g-C3N4) composite PCM, prepared using the confinement method, PEG hinders the crystallization of PLA, and it was confirmed using the XRD method. The authors found that the incorporation of PEG changed the number of diffraction peaks of PLA, suggesting disrupted PLA crystallization, and in consequence a decrease in hardness [29]. The composite PCM exhibited a heat of phase transition of 106.1 kJ/kg for PLA:PEG:g-C3N4 with a mass ratio 3:6:1, and an increased thermal conductivity compared to PLA.…”
Section: Discussionmentioning
confidence: 99%